Impact of simulation experiences on learning transfer in new graduate registered nurses. - Anderson, Lori S. (East Carolina University, 2015)
The purpose of this study was to evaluate the influence of pre-work factors (healthcare experience, type of education, type and frequency of simulation exposure) and work factors (type and frequency of simulation exposure) on perceptions of transfer of learning, confidence and competence development, and RN role preparedness. The study participants consisted of 251 new graduate registered nurses obtained from the North Carolina Board of Nursing (NCBON) registered nurse licensure database. A descriptive correlation design was utilized to explore the impact of simulation on perception of gains in transfer of learning, confidence and competence development, and RN role preparedness. Frequencies and percentages, independent t-tests, and Pearson product-moment correlation were applied to the data set. The study results showed simulation activities occurred more frequently in pre-licensure programs compared to new nurse orientation programs, and higher transfer of learning gains were noted in those nurses who participated in both pre-licensure and orientation simulation activities. Further, simulation exposure in both programs had positive influences on confidence, competence, RN role preparedness and pre-licensure transfer of learning. For nurses with both pre-licensure and new nurse orientation simulation experience, moderate to strong correlations were observed in associate degree nurses, with and without previous healthcare experience, and in bachelor degree nurses with previous healthcare experience. Further research is needed on a larger representation of advanced beginner new graduates. Ideally, transfer of learning and new nurse outcome measures should be evaluated with a more diverse, national representation of new graduates. Continued research on simulation-based orientation experiences is needed as more hospitals are implementing this strategy into their new nurse transition programs.
Keywords: Nursing; New graduate registered nurse; Simulation; Transfer of learning; Nurses; Transfer (Psychology); Competency-Based Education--methods; Patient Simulation